Wealth Inequality in a Time of Transition: Coastal Flanders in the Sixteenth Century - Dombrecht, Kristof; Ryckbosch, Wouter (TSEG - The Low Countries Journal of Social and Economic History, 2017)
In this article we aim to make a case for a renewed attention to the structural social and political processes that influenced changes in early modern levels of inequality. We argue that early modern changes in inequality were not solely, or even primarily, determined by (exogenous) demographic trends and macro-economic growth, but by structural changes in the (political) economy of early modern society. By studying a micro-level case-study of inequality during a period of intense change in economic structure, this article aims to reconcile such traditional interpretations with the recent historiography on early modern inequality.